Digitalization and Social Da‘wah: Innovative Models of Islamic Community Development in the Era of Digital Transformation - Happy Agustiani (Al-Jamahiria : Jurnal Komunikasi dan Dakwah Islam, 2025)
Artikel ini mengkaji transformasi dakwah Islam dari praktik konvensional ke format berbasis digital sebagai respons terhadap perkembangan teknologi komunikasi, perubahan sosial, serta kebutuhan spiritual masyarakat Muslim kontemporer. Dakwah digital tidak hanya muncul sebagai medium penyebaran ajaran Islam, tetapi juga sebagai instrumen strategis dalam pemberdayaan masyarakat, termasuk peningkatan literasi keagamaan, keterlibatan generasi muda, serta penguatan sosial dan ekonomi melalui platform digital. Penelitian ini menggunakan metode kualitatif dengan pendekatan studi pustaka yang dianalisis melalui teknik analisis isi. Artikel ini  menunjukkan bahwa digitalisasi dakwah menawarkan peluang signifikan, seperti peningkatan efisiensi jangkauan, kolaborasi komunitas, serta pembentukan narasi Islam moderat di ruang digital. Namun demikian, dakwah digital juga menghadapi tantangan substansial, antara lain ketimpangan akses digital, maraknya disinformasi keagamaan, serta keterbatasan kapasitas profesional sebagian dai yang beroperasi di media sosial. Temuan penelitian ini merekomendasikan penguatan literasi keagamaan digital, pembentukan standar profesional bagi dai digital, serta penguatan platform dakwah digital berbasis komunitas guna menjamin keberlanjutan dan dampak transformatif pengembangan masyarakat Islam di era digital. This study examines the transformation of Islamic da‘wah from conventional practices to digital-based formats in response to developments in communication technology, social change, and the evolving spiritual needs of contemporary Muslim communities. Digital da‘wah has emerged not only as a medium for disseminating Islamic teachings but also as a strategic instrument for community empowerment, including enhancing religious literacy, youth engagement, and socio-economic strengthening through digital platforms. This research employs a qualitative method with a literature-based approach, analyzed using content analysis techniques. The findings indicate that the digitalization of da‘wah offers significant opportunities, including greater outreach efficiency, community collaboration, and the construction of moderate Islamic narratives in digital spaces. Nevertheless, digital da‘wah also faces substantial challenges, including digital inequality, the proliferation of religious misinformation, and the limited professional capacity of some preachers operating on social media. This study recommends strengthening digital religious literacy, establishing professional standards for digital preachers, and reinforcing community-based digital da‘wah platforms to ensure the sustainability and transformative impact of Islamic community development in the digital era.Keywords: digital da'wah, religious literacy, Islamic moderation, da'wah technology, social transformation.